Learning from Mental Health Lived Experience and the Influence on Students' Practice. Issue 3 (3rd July 2017) - Ridley, Sophie; Martin, Robyn; Mahboub, Lyn
ABSTRACT: This study explored how learning from mental health lived experience influenced Australian social work students' practice during their first fieldwork placement. Involvement of mental health consumers in social work education is gaining momentum, yet little is known about how this type of learning informs students' practice. Ten social work students participated in semistructured interviews and one focus group. Findings suggest that learning from lived experience promoted social work practice that honoured the expertise of mental health consumers and privileged personal recovery. Factors such as organisational culture and supervisor attitudes were found to mediate the students' attempts to privilege lived experience.